Seven years to seven figures : - Masterson, Michael (John Wiley & Sons, 2006)
In Seven Years to Seven Figures, self-made millionaire and renowned wealth coach Michael Masterson reveals the steps you can take to accumulate seven-figure wealth within seven years—or less. Seven Years to Seven Figures will give you the tools to increase your income, get the highest possible returns on investments, save wisely—and secure your financial future faster than you may have ever dreamed.